2017
DOI: 10.1007/s13193-017-0682-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasma D-Dimer Levels in Breast Cancer Patients and Its Correlation with Clinical and Histopathological Stage

Abstract: Breast cancer, the most common female malignancy, represents a heterogeneous group of tumors, which presen both varied behaviors and response to therapy. This study was done with an attempt to evaluate the role of D-dimer in patients of carcinoma breast, in predicting lymph node metastasis in carcinoma patients and to look for relationship of these markers with histopathologic parameters. Clinical data was obtained from clinical examination of patients admitted in the Department of Surgery with history of brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Studies have shown that the level of D-dimer is related to the occurrence of breast cancer, is an independent factor in the prognosis of breast cancer, and is associated with distant metastasis of breast cancer. 24 Levitan and other scholars have pointed out that thromboembolism in cancer patients is 6 times that of normal people. Thromboembolism can lead to hypercoagulability of blood, damage to blood vessels and slow blood flow.…”
Section: D-dimer and Plasma Fibrin Degradation Products (Fdps)mentioning
confidence: 99%
“…Studies have shown that the level of D-dimer is related to the occurrence of breast cancer, is an independent factor in the prognosis of breast cancer, and is associated with distant metastasis of breast cancer. 24 Levitan and other scholars have pointed out that thromboembolism in cancer patients is 6 times that of normal people. Thromboembolism can lead to hypercoagulability of blood, damage to blood vessels and slow blood flow.…”
Section: D-dimer and Plasma Fibrin Degradation Products (Fdps)mentioning
confidence: 99%
“…The release and activation of various tumor-associated coagulation factors, such as tissue factor, fibrin, and fibrinolytic enzymes 20 , can potentiate the coagulation system and trigger a cascade of coagulation reactions through different signaling pathways 21 . Several types of tumors, including lung 8 , prostate 22 , cervical 23 , breast 7 , and colorectal malignancies 11 , exhibit elevated levels of D-dimers, excluding those with clinical thrombosis. The dysregulation of the coagulation system may serve as an early indication of tumor cell proliferation and a significant marker of occult tumors or residual tumor cells that persist in the body after chemotherapy and remain dormant for years 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lower D-dimer levels may have inactive tumors and smaller tumor volumes. Elevated plasma D-dimer levels predict an increased risk of tumor recurrence and a poorer prognosis, according to data from a retrospective cohort analysis of patients with epithelial carcinoma of the upper urinary tract by Chen et al D-dimer levels have been shown to be useful in assessing the treatment and prognosis of a wide variety of malignancies 35 , including colorectal and uroepithelial malignancies 11,35 , as well as gastric 9,19,36 , lung 37 , breast 7,25 , cervical cancers 23 , and high-grade musculoskeletal sarcoma 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation